Why Safety Policies Fail in High-Risk Public Organizations: An Implementation Governance Perspective from the Power Generation Sector - A Jusriadi; Andi Aslinda; Rifdan; Didin Hafid (Journal of Indonesian Scholars for Social Research, 2025)
The failure to implement occupational safety and health (OSH) policies remains a persistent problem in high-risk public organizations, even though a comprehensive regulatory framework and operational standards are in place. This article aims to analyze why OSH policies fail to be implemented effectively in high-risk public organizations using the perspective of implementation governance. This study uses a qualitative approach through case studies in the power generation sector, with data collection techniques in the form of in-depth interviews, observations, and policy document analysis. The analysis is based on a policy implementation framework that emphasizes the interaction between policy objectives, resources, organizational characteristics, implementer disposition, and communication patterns. The findings show that the failure of OSH policies is not solely due to weak individual compliance, but rather to the discontinuity of implementation governance at the operational level. This study contributes to the enrichment of the policy implementation literature by repositioning OSH as a matter of public organization governance, not merely regulatory compliance.